2007
DOI: 10.1038/sj.eye.6702789
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of macular retinal thickness and volume in normal eyes and highly myopic eyes with third-generation optical coherence tomography

Abstract: Purpose To compare the macular retinal thickness and macular volume between subjects with high myopia and non-myopia. Methods This prospective nonrandomized, comparative study recruited healthy subjects with high myopia subjects, defined as a spherical equivalence (SE) over À6 dioptres (D) or AXLX26.5 mm and the best corrected visual acuity better than 20/25, and subjects with non-myopia, defined as an with SE between 1.5D and À1.5 D and the BCVA better than 20/25. Optical coherence tomography was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
134
8
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(164 citation statements)
references
References 21 publications
18
134
8
4
Order By: Relevance
“…In contrast, we found thinner central macular thickness in shorter and more hyperopic eyes. These results are in agreement with those provided by other researchers in both adults 28 and children. 8 Wu et al 28 reported that RT in individuals with high myopia and long eyes was thicker in the foveola and fovea, but thinner in the inner and the outer macular regions.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…In contrast, we found thinner central macular thickness in shorter and more hyperopic eyes. These results are in agreement with those provided by other researchers in both adults 28 and children. 8 Wu et al 28 reported that RT in individuals with high myopia and long eyes was thicker in the foveola and fovea, but thinner in the inner and the outer macular regions.…”
supporting
confidence: 83%
“…These authors also showed smaller macular volume in subjects with high myopia. 28 Lim and Chun 8 also obtained thinner macular thickness and lower macular volumes in high myopic children. It has been suggested that these relations would be owing to the mechanical globe elongation linked with myopia, resulting in retinal stretching and thinning.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Retinal thickness in highly myopic eyes (>6D) was higher in the fovea, but lower in the inner and outer regions compared to non-myopic eyes in a study with age-matched groups (Wu et al, 2008). Thus it may be an indication for change in retinal contour of highly myopic eyes and care is needed while interpreting macular pathology on OCT scans of such eyes.…”
Section: Oct Interpretation -Quantitative Analysismentioning
confidence: 99%